METODE BERCERITA (STORRY TELLING) PADA PENGAJARAN ANAK USIA DINI (STUDI PADA PAUD SATU ATAP WAY PERANCANG ABUNG KUNANG LAMPUNG UTARA) - JUNAIDAH, JUNAIDAH (Universitas Islam Negeri Raden Intan Lampung, 2017)
Abstract Early childhood education (PAUD) is the level of education before basic education which is a coaching effort aimed at children from birth up to the age of six years done through the provision of educational stimulus to help growth and physical and spiritual development so that children have readiness in entering education further, organized on formal, nonformal, and informal channels. Early childhood education (0-8 years) is an education that has different characteristics with other children of age, so that education also needs to be regarded as something that is devoted, including the appropriate method. Teaching methods in early childhood is very varied, including story telling, singing, playing, rhyming and tour work. Each method has weaknesses and advantages. The use of one of the selected methods is certainly adapted to the condition of the school or the ability of a teacher in applying it. Storytelling can be used as a method to convey the values prevailing in society, in addition to simple also has many conveniences. The purpose of writing is to find and define the meaning, form and techniques of good storytelling in early childhood learning, knowing the implementation of the storytelling method that is implemented in the early one week. The storytelling technique of PAUD Permata Indah is a teacher reading many story books, taking much experience and from everyday events. Sometimes stories or tales are drawn from social media and you tube, as often as possible to chat with students so as to understand the child's language style, to understand what the child likes and maximize expression when telling stories in repetitive sections. The form of the story there are two namely with props and without props. Keywords: The method of telling the story of early childhood, early childhood education Satu Atap Way Perancang